A 'world culture' of institutional ambiguity? Comparing the reorganization of hospital care in Germany and Mexico. (May 2015) - Bode, Ingo
According to widespread perceptions, health care provision is becoming more universalistic internationally – but also more business-like. The article examines this dual movement through the lens of the (neo-institutionalist) world polity model and by exploring regulatory change in the hospital sectors of Mexico and Germany. These – highly disparate – countries have both seen attempts to make the access to inpatient care more comprehensive, quantitatively or qualitatively; at the same time, reforms have led to the marketization and managerialist transformation of their health care infrastructures. Hence there is similar regulatory change being driven by two expansive institutional logics, although its implementation faces contingencies, due to country-specific bottlenecks in the reform process. In this configuration, hospital care undergoes a process of 'fuzzy' reorganization with paradoxical consequences. The overall development bears witness to a cross-national diffusion of institutional ambiguity to which macro-sociological theory concerned with globalization should pay greater attention.